Evaluating Habitat of Houbara Bustard (Chlamydotis Undulata) Through Trending of Vegetation Activity in Cholistan Desert of Pakistan - Mukhtar, Rabia; Abbas, Sunaina; Saqib, Zafeer; Ashraf, Arshad (International Journal of Environment, 2021)
In the present study, the habitat of Houbara Bustard was evaluated in Lal Suhanra National Park (LSNP) of Cholistan desert, Pakistan using remote sensing data of LANDSAT-5 and MODIS hyper-temporal vegetation index data of 2000-2012 period. Trend analysis of Normalized Difference Vegetation Index was performed using seasonal Mann-Kendall test to understand the distribution and projected status of the habitat. Over 76% area of the LSNP comprising of sand dunes, sandy/open shrubs, sandy (barren) and open shrubs was identified as the most suitable habitat for Houbara. Majority of the LSNP area exhibited stable trend in land cover/vegetation activity, e.g. about 7% land cover indicated progressive and 4% regressive trend, while 89% land cover exhibited stability (significant at p